Investigation on mechanical properties and tribological behaviour of stir cast LM13 aluminium alloy based particulate hybrid composites. Issue 7 (11th July 2019) - Chelladurai, S.J.S.; Murugesan, T.; Rajamani, T.; Anand, S.; Asok, S.J.P.; Kumaravel, S.
Abstract: LM13 aluminium alloy with boron carbide (0 wt.%–7.5 wt.%) and fly ash (2.5 wt.%) reinforced particulate hybrid composites were fabricated using liquid metallurgy route. Microstructure and mechanical properties viz., hardness, ultimate tensile strength and ductility were investigated. Wear behaviour of composites was tested by varying sliding distance and load. Fracture surface and worn surface of composites were examined using field emission scanning electron microscope. Microstructure of hybrid composites revealed uniform dispersion of particles in LM13 aluminium alloy. Hardness and tensile strength of composites increased with increasing wt.% of boron carbide and fly ash particles. Wear test results showed that addition of particles significantly decreased the weight loss and coefficient of friction. Also cumulative weight loss decreased up to 47.2 % for 10 wt.% of hybrid composites as compared to LM13 aluminium alloy. Fracture surface of composites showed dimples with particle cracking on the surface. Worn surface of LM13 aluminium alloy showed continuous grooves due to ploughing with delamination. However, worn surface of composites showed fine grooves due to the presence of hard reinforcements on the surface. Boron carbide and fly ash reinforced LM13 aluminium hybrid composites exhibited superior mechanical properties with excellent wear resistance as compared to LM13 aluminium alloy.